2013
DOI: 10.4081/jnai.2013.e2
|View full text |Cite
|
Sign up to set email alerts
|

A new entropy model for RNA: part II. Persistence-related entropic contributions to RNA secondary structure free energy calculations

Abstract: In previous work, we have shown that the entropy of a folded RNA molecule can be divided into local and global contributions using the cross-linking entropy (CLE) model, where, in the case of RNA, the crosslinks are the base-pair stacking interactions. The local contribution to the CLE is revealed in the Kuhn length (a measure of the stiffness of the RNA). The Kuhn length acts as a scaling parameter. When the size of the system is rescaled, the relationship between local and global free energy must be renormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The Tm of G-C double-stranded oligonucleotides was calculated using the Crosslinking Entropy (CLE) Method [45,46]. According to this method the Tm of these molecules at the concentration here used of 1.3 M is, when fully paired, 86 °C.…”
Section: The Ligation Following Intermolecular Cleavage (Lic) Mechanismmentioning
confidence: 99%
“…The Tm of G-C double-stranded oligonucleotides was calculated using the Crosslinking Entropy (CLE) Method [45,46]. According to this method the Tm of these molecules at the concentration here used of 1.3 M is, when fully paired, 86 °C.…”
Section: The Ligation Following Intermolecular Cleavage (Lic) Mechanismmentioning
confidence: 99%
“…Upon protein structure modeling we have shown that the term responsible for the persistent length does not make a large contribution to the calculations of the loop entropy (the persistent length 20 Å) [6]. The persistence length for RNA molecules is ~10-20 Å [43], and therefore here we ignore this parameter (the term itself is not so strict and can be largely treated as a constant in the first approximation [44]). …”
Section: Estimation Of Free Energy and Calculation Of Folding Nucleimentioning
confidence: 99%